Spherical rolling robot for planetary surface exploration - Lim, Chee Shiong (2015)
With today’s technology, robots with navigation and vision abilities are often developed to aid security surveillance and rescue missions. Among those, spherical rolling robot (SRR), is an invention based on a concept of producing and controlling the rolling motion of a sphere. Over the years, SRRs have shown promising results. Generally they are able to navigate on most kinds of surfaces. They have many advantageous characteristics that make them reliable and efficient in navigational tasks. What makes them stand out from others? It is their spherical body shape. Why? Firstly, a sphere is easy to be moved and always remains at the same shape once moved hence it can provide a holonomic system. Holonomic system is ideal for navigational robot as it enables the robot to be always at starting position regardless of body orientation. Given such agility, SRRs can access into more kinds of human-unfriendly environment. Besides that, internal hardware is well protected from external physical disturbances by the spherical shell. This makes SRR very durable. These have motivated many to focus on developing spherical bodied robots including the author of this report. This report introduced the design and development of an SRR which uses a 1-DOF internal pendulum mechanism to roll forward and backward, under closed loop control system. Dynamic analyses of the system and real time simulation results have also been demonstrated in this report.